Pembiayaan Usaha Mikro Kecil Dan Menengah (UMKM) Sebagai Solusi Dalam Meningkatkan Perkembangan Usaha (Studi Kasus Pada UMKM Distrik Aimas Kabupaten Sorong) - fensca lahallo; Samuel Y. Warella (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The purpose of this research is to compare the development of Micro, Small and Medium Enterprises (MSMEs) before and after obtaining financing (Case Study on UMKM, Aimas District, Sorong Regency). This research is a development of the results of previous author's dedication to the same subject, namely the fundamental problem of a lack of capital and access to capital sources is very difficult. This type of research is comparative research. The sample of this research is MSME actors who have received financing from both financial institutions, cooperatives, local governments, and other non-bank financial institutions for about 1 year. Data analysis to be carried out is the normality test and the Wilcoxon test. The results showed that of all the indicators studied, namely business capital, sales turnover, profit, labor, business branches, production / sales capacity and the number of customers using the Wilcoxon sign test showed that the indicators of business capital and the number of customers had significant differences before and after obtaining financing, while other indicators, namely sales turnover, profit, manpower, business branches, and production / sales capacity do not have a significant difference.